Explorando a criatividade e a sensibilização ambiental no Ensino Fundamental por meio da robótica sustentável - REIS, Everson Jyan Brasil (2024)
This work describes an Environmental Education (EE) project using sustainable robotics as a didactic tool. The aim was to promote environmental awareness and the pedagogical use of sustainable robotics, involving both Full-time High School students and regular education students. The project was divided into two phases, carried out in state schools in the municipality of Capanema, Pará. In the first phase, theoretical and practical activities were developed with sustainable robotics experiments, using recyclable and reusable materials. In the second phase, students had autonomy in choosing and assembling prototypes, demonstrating greater interaction and creativity. The results showed active participation from students, promoting skills such as creativity and problem-solving, in pursuit of possible ways to minimize waste impact in the school environment. The interdisciplinary approach enabled the connection between different areas of knowledge and awareness of the importance of sustainability. The continuity of the project reinforced environmental awareness and the pursuit of sustainable solutions in the school context, as well as providing a simple and accessible way for education to take place in various areas of knowledge. The practical approach of sustainable robotics allowed students to directly experience the benefits of recycling and reusing materials. In other words, the Environmental Education project using sustainable robotics not only fulfilled its main objective of sensitizing students to environmental issues but also demonstrated how the use of sustainable robotics can favor its pedagogical use for teaching other curriculum components: physics, chemistry, mathematics, discussing how technologies have transformed pedagogical practice, providing meaningful and dynamic learning.